Exendin-4 Inhibits Matrix Metalloproteinase-9 Activation and Reduces Infarct Growth After Focal Cerebral Ischemia in Hyperglycemic Mice. Issue 5 (May 2016) - Kuroki, Takuma; Tanaka, Ryota; Shimada, Yoshiaki; Yamashiro, Kazuo; Ueno, Yuji; Shimura, Hideki; Urabe, Takao; Hattori, Nobutaka
Abstract : Background and Purpose—: Admission hyperglycemia is an independent risk factor for poor outcome of ischemic stroke. Amelioration of hyperglycemia by insulin has not been shown to improve the poststroke outcome. Glucagon-like peptide 1 receptor agonists, which modulate glucose levels by stimulating insulin secretion, have been shown to exert cytoprotective effects by inhibiting inflammation and oxidative stress. This study aimed to evaluate whether the glucagon-like peptide 1 receptor agonist exendin-4 could reduce glucose levels and exert protective effects after acute focal ischemia in hyperglycemic mice. Methods—: Hyperglycemia was induced by intraperitoneal injection of dextrose 15 minutes before transient middle cerebral artery occlusion was performed for 60 minutes using an intraluminal thread. We assessed 4 groups: (1) normal glucose (vehicle control), (2) induced hyperglycemia, (3) induced hyperglycemia with insulin treatment, and (4) induced hyperglycemia with exendin-4 treatment. Neurovascular injuries in brains from each group were evaluated 24 hours and 7 days post ischemia. Results—: Hyperglycemia significantly increased infarct volume (36.3±1.20 versus 26.9±1.28; P <0.001), brain edema ( P <0.05), and hemorrhagic transformation compared with control ( P <0.001). This increase in infarct volume was associated with increased blood–brain barrier disruption and matrix metalloproteinase-9 activation. Exendin-4, but not insulin, attenuated matrix metalloproteinase-9 activation, proinflammatory cytokine (tumor necrosis factor-α) release, and biomarkers of oxidative stress and showed significant inhibition of infarct growth at 24 hours (23.6±0.97 versus 36.3±1.20; P <0.001) and at 7 days after ischemia (21.0±0.92 versus 29.3±1.41; P <0.001). Conclusions—: Treatment with exendin-4 could be a potentially useful therapeutic option for treatment of acute ischemic stroke with transient hyperglycemia.